Situational analysis study for the agriculture sector in Ghana - Essegbey, George Owusu; MacCarthy, Dilys Sefakor (2020)
Agriculture is important for Ghana’s economy and the livelihoods of the majority of the rural population even though its level of contribution to GDP is declining. Its importance is not only in terms of the contribution to food and nutrition security, but also in providing a basis for agro-industrial activities and for exports. It provides jobs and livelihoods to a significant proportion of the population especially in the rural areas. Farmers cultivate major staples such as maize, cassava, yam, plantain, sorghum and rice. The cash crops grown include cocoa, oil palm, cashew and rubber among others. Ghana’s 2019 annual growth rate for agriculture was 4.6%. The crop sub-sector is the largest in the agricultural sector followed by livestock and fisheries. The impacts of climate change on agriculture are not just projected but are real. The sector is currently contending against erratic rainfall patterns, water stress, desertification/ degradation of ecological systems/ forest degradation; increasing temperatures; and disruption of seasonality. Climate change affects agricultural activities in diverse ways including changes in the onset of the rainy season, increase incidence and frequency in some regions, increase in post-harvest losses of agricultural commodities, decline in the availability and quality of forage and high mortality and morbidity of livestock. Managing the impacts of climate change is important in addressing the challenge of enhancing productivity in the agricultural sector. It is a multi-dimensional challenge; hence solutions must emanate from the identifiable components of the environment. Agriculture is given a high priority in Ghana’s political and socio-economic discourse with the President highlighting the agricultural programme of PFJ as the flagship of his government. The various national policy documents including the national development framework have underscored the importance of the agricultural sector. However, there is need to enhance policy coherence and strengthen policy implementation along the governance structures from the national through the regional to the municipal and district assemblies. Farmers and women must have stronger voices at the district level to articulate better their concerns. Besides, Ghana’s national budgetary allocation to the agricultural sector is still below the target of the Maputo Declaration at about 9.7% currently. However, the on-going programmes such as the PFJ and its constituent modules are likely to increase it. The funding from multi- and bilateral sources are also likely to increase agricultural expenditures. The key recommendations proposed include creating an enabling legal, institutional and policy framework to create a favorable environment for enhancing policy coherence and strengthening policy implementation along the governance structures from the national to regional through to the municipal and district assemblies. It is also important to increase national budgetary and finance flows from bilateral and multi-lateral sources into the agriculture sector to promote widespread adoption of Climate Smart Agriculture (CSA). Investments should take into account gender and youth considerations, supported by a strong extension services system. Farmers’ adoption of CSA is an important intervention area that economic planning must cater for. Market access and access to financial resources to finance their agricultural activities in crops, livestock, fishery and agroforestry, are crucial. Government must consider, adopt and implement this recommendation in collaboration with other stakeholders.